EFEKTIVITAS TELEMEDICINE DALAM MENINGKATKAN KEPATUHAN PASIEN TERHADAP PENGOBATAN PENYAKIT KRONIS DI INDONESIA: SYSTEMATIC LITERATUR REVIEW - Dewi, Siti Handam; Alfauzain, Alfauzain; Ilahi, Vitratul; Ashari, Muhammad Al; Juliandi, Jeri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to evaluate the effectiveness of telemedicine in improving patient adherence to chronic disease treatment in Indonesia. Chronic diseases such as diabetes, hypertension, heart disease, and stroke are leading causes of morbidity and mortality in Indonesia. Patient adherence to long-term treatment is crucial to prevent serious complications. Telemedicine, as a solution to improve access and quality of healthcare, has gained popularity in Indonesia, especially after the COVID-19 pandemic. This study employs a Systematic Literature Review (SLR) method, identifying literature from PubMed, Scopus, Google Scholar, Garuda (Indonesia), and ScienceDirect databases from 2020 to 2025. Eight relevant articles were selected based on strict inclusion and exclusion criteria. The findings indicate that telemedicine is effective in improving patient adherence to chronic disease treatment. Improved accessibility, automatic medication reminders, regular check-up notifications, and the convenience of remote consultations are key factors contributing to enhanced patient adherence. However, challenges such as limited access to technology and infrastructure in remote areas, as well as the lack of physical interaction between patients and doctors, remain significant barriers. This study concludes that, although telemedicine offers many benefits, its implementation in Indonesia still faces substantial challenges that need to be addressed through supportive policies, improved technology infrastructure, and patient education regarding the benefits and use of telemedicine.Keywords: Effectiveness, Telemedicine, Chronic Disease, Literature Review